Insights on the use of dolphins (boto, Inia geoffrensis and tucuxi, Sotalia fluviatilis) for bait in the piracatinga (Calophysus macropterus) fishery in the western Brazilian Amazon - Iriarte, V.; Marmontel, M. (J. Cetacean Res. Manage., 2023)
In the Amazon Basin, the use of the pink dolphin or boto (Inia geoffrensis) for bait in the piracatinga (Calophysus macropterus) fishery was first detected in the year 2000. Since then, this artisanal fishery has become more prevalent as it requires only a few hours of work per night and provides immediate cash earnings. It is thus an attractive addition to (or replacement for) traditional fishing. Previous reports have noted the use of botos as bait, but stated that the most common bait used are caimans (Melanosuchus niger, Caiman crocodilus). Estimates of the number of dolphins killed based on fish landings have been proposed and an apparent decrease in sighting/survival of an artificially-marked boto population was observed. Although stocks/population estimates, trends and actual numbers of hunted dolphins are unknown, the conservation impacts of this activity are of concern. Between October 2010 and November 2011, research was conducted within an area with serious conflicts between dolphins and fishermen as well as intense fishing for piracatinga, i.e. in the lower Japurá River, on the border with the Mamirauá and Amanã Sustainable Development Reserves, where both boto and tucuxi (Sotalia fluviatilis) are used for bait. One-hundred and fifty-seven monitoring surveys were carried out in eight key communities, confirming 114 piracatinga fishing events through direct monitoring and incognito surveys of fishing gear (gaiolas). Empirical evidence of the activity in gaiolas comprised pieces of bait, carcass remains, piracatinga provoked vomits and dolphin fished carcasses. Of those, 31.2% (n = 35) involved cetacean bait (91.4% I. geoffrensis, 8.58% S. fluviatilis), 68.7% (n = 77) caiman bait (96% M. niger, 4% C. crocodilus), and two fishing events used both types. These percentages may be higher/lower in other areas within and outside the Reserves. Given the increasing trend of the piracatinga fishery, the authors believe that precautionary measures for the conservation of Amazonian dolphins are urgently needed. Development of practical short-term solutions (e.g. offal-baited fish traps) and multispecies management together with law enforcement, incentives and educational programmes could allow the future transition of riverine communities from the piracatinga fishery to sustainable, higher income activities.